2007
DOI: 10.1007/s10832-007-9052-3
|View full text |Cite
|
Sign up to set email alerts
|

Study by laser interferometry of the resonance modes of the shear plate used in the standards characterization of piezoceramics

Abstract: Recent Finite Element Analysis (FEA) modeling of a Standard shear plate of Navy II type PZT-based ceramics was carried out based on the full matrix material characterization Material coefficients in the linear range, including all losses, were obtained by an iterative automatic method from impedance measurements at resonance. FEA modeling has shown that the shear plate used in the standard characterization of piezoceramics is dynamically clamped at resonance, which results in an underestimation of the related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Such spurious resonances were generally, and erroneously according to the FEA results, associated to microstructural or poling inhomogeneities of the piezoceramic. The dynamical clamping of the Standard shear sample, that was previously suggested by other authors [25], is revealed by FEA modelling [23] and has also been verified by laser interferometry measurements [26]. This finding also helped to explain why the use of the Standard shear geometry led to underestimation of the shear piezoelectric coefficients.…”
Section: Introductionsupporting
confidence: 67%
“…Such spurious resonances were generally, and erroneously according to the FEA results, associated to microstructural or poling inhomogeneities of the piezoceramic. The dynamical clamping of the Standard shear sample, that was previously suggested by other authors [25], is revealed by FEA modelling [23] and has also been verified by laser interferometry measurements [26]. This finding also helped to explain why the use of the Standard shear geometry led to underestimation of the shear piezoelectric coefficients.…”
Section: Introductionsupporting
confidence: 67%
“…3-right). Measurements of normal displacement to the surface of the Standard shear resonator by laser interferometry have confirmed that the modes of motion of the Standard shear sample are a composition of plane waves and the inhomogeneous shear displacement [34]. These results also reveal the dynamical clamping as the source of the underestimation of the material parameters when using Standard shear items.…”
Section: Matrix Characterization Of Piezoceramics Using Non-standard mentioning
confidence: 63%
“…On the one hand, longitudinal poling is a problem when dealing with materials of a high coercive field [ 11 ] or low dielectric breakdown [ 12 ]. On the other hand, the coupling of shear modes and other lateral and contour modes, which takes place in the shear resonance of standard length-poled shear plates, is unavoidable [ 3 , 4 , 13 , 14 ]. Unfortunately, this leads to the stringent requirement of aspect ratios between the length for poling ( L ), the width ( w ), and the thickness for electrical excitation ( t ) of the plate of L , w > 20 t [ 15 ] and to an underestimation of the piezoelectric coefficients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%